Isolation and Characterization of a Thermaerobacillus caldiproteolyticus-like Strain Producing Extracellular Amylase from the Nelumwewa Geothermal Spring, Sri Lanka - Sarath Bandara; Buddhika Dharmasena; Lakshani Pathirana; Prasad Jayasooriya; Aruna Weerasooriya (Fermentation, 2025)
The growing demand for efficient sustainable biocatalysts for industrial applications has driven the exploration of extremozymes from extremophiles, particularly those thriving in geothermal environments. This study aimed to isolate and characterize extracellular amylase-producing thermophilic bacteria from the Nelumwewa geothermal spring in Sri Lanka, an underexplored ecosystem. Among the isolated thermophilic bacterial strains, NW2 isolates exhibited a prominent extracellular amylase activity. Molecular characterization by 16S rRNA gene sequencing confirmed the close phylogenetic relationship between NW2 and Thermaerobacillus caldiproteolyticus, which is well-known for thermostable proteases. Biochemical assays revealed optimal amylase activity of NW2 isolate at 60 °C and pH 8.0, with a crude enzyme activity of 0.85 U/mL. The enzyme demonstrated efficient hydrolysis of raw cassava starch, highlighting its potential for industrial applications in food, biofuel, and detergent industries. This study reports the first T. caldiproteolyticus-like strain from Sri Lanka with significant extracellular amylase activity, emphasizing the biotechnological potential of geothermal springs as sources of novel extremozymes. These findings contribute to the growing repository of thermostable enzymes, highlighting the need for further exploration of Sri Lanka’s geothermal microbial diversity for industrial biocatalysts.